2021
DOI: 10.3389/fnbeh.2021.693362
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota in Depression: A Focus on Ketamine

Abstract: According to the WHO, major depressive disorder is the leading cause of disability worldwide, and it is a major contributor to the overall global burden of disease. The pathophysiology of this common and chronic disease is still not completely understood. The gut microbiome is an increasingly recognized environmental factor that can have a role in depression, acting through the gut–microbiota–brain axis. The available treatment for depression is still insufficient since 30% of patients are treatment-resistant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 92 publications
(114 reference statements)
0
16
0
Order By: Relevance
“…For instance, the reported increase of the genus Lactobacillus after the final ECT session in Kanayama et al (2021) might (also) be ascribed to ketamine, which was used as an anesthetic during ECT sessions and has been shown to increase the abundance of Lactobacillus in rats in low doses (2.5 mg/kg). Thus, it is unclear whether this increase was due to induction of seizures and/or to ketamine's effects on the gut microbiota (Wilkowska et al, 2021). Similarly, Lubomski et al (2022) found initial alterations in several bacteria (i.e., Clostridium_XlVa, Bilophila, Pseudoflavonifractor, Dorea) that did not sustain after four weeks of DBS treatment.…”
Section: Which Mechanisms Could Underly Neuromodulation-induced Chang...mentioning
confidence: 99%
“…For instance, the reported increase of the genus Lactobacillus after the final ECT session in Kanayama et al (2021) might (also) be ascribed to ketamine, which was used as an anesthetic during ECT sessions and has been shown to increase the abundance of Lactobacillus in rats in low doses (2.5 mg/kg). Thus, it is unclear whether this increase was due to induction of seizures and/or to ketamine's effects on the gut microbiota (Wilkowska et al, 2021). Similarly, Lubomski et al (2022) found initial alterations in several bacteria (i.e., Clostridium_XlVa, Bilophila, Pseudoflavonifractor, Dorea) that did not sustain after four weeks of DBS treatment.…”
Section: Which Mechanisms Could Underly Neuromodulation-induced Chang...mentioning
confidence: 99%
“…In addition, gut microbiota can significantly affect intestinal mucin, especially Akkermansia muciniphila , which can significantly improve the thickness of mucin [ 7 ]. The gut microbiota can affect host health and is associated with multiple diseases, such as diabetes and depression [ 8 , 9 ]. The colonization or increase of probiotics is beneficial to the treatment of diseases [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine is a new and effective antidepressant in treatment-resistant individuals. It is recognized that the antidepressant impact of ketamine might be partially mediated by the modification of gut microbiota [ 24 ]. However, antidepressants are not the first-line treatment in cases of mild depression.…”
Section: Introductionmentioning
confidence: 99%